PHARMACOLOGICAL TREATMENTS FOR TINNITUS: NEW AND OLD - Salvi, R. (2009)
Subjective tinnitus, the phantom ringing or buzzing sensation that occurs in the absence of sound, affects 12–14% of adults; in some cases the tinnitus is so severe or disabling that patients seek medical treatment. However, although the economic and emotional impact of tinnitus is large, there are currently no FDA-approved drugs to treat this condition. Clinical trials are now underway to evaluate the efficacy of N-methyl-d-aspartate (NMDA) and dopamine D(2) antagonists, selective serotonin reuptake inhibitors (SSRIs), γ-aminobutyric acid (GABA) agonists and zinc dietary supplements. Previous off-label clinical studies, while not definitive, suggest that patients with severe depression may experience improvement in their tinnitus after treatment with antidepressants such as nortriptyline or sertraline. A small subpopulation of patients with what has been described as “typewriter tinnitus” have been shown to gain significant relief from the anticonvulsant carbamazepine. Preliminary studies with misoprostol, a synthetic prostaglandin E1 analogue, and sulpiride, a dopamine D(2) antagonist, have shown promise. Animal behavioral studies suggest that GABA transaminase inhibitors and potassium channel modulators can suppress tinnitus. Additionally, improvements in tinnitus have also been noted in patients taking melatonin for significant sleep disturbances. Like other complex neurological disorders, one drug is unlikely to resolve tinnitus in all patients; therapies targeting specific subgroups are likely to yield the greatest success.